Global Trade Tensions, Capital Structure, and Firm Value: Evidence from Multinational Companies Listed on the Indonesia Stock Exchange - Udyono, Udyono; Rajaman, Rajaman; Razak, Muhammad Maula (Dinasti Publisher, 2026)
Global trade tensions are a critical issue with significant implications for multinational corporations. This study aims to analyze the influence of global trade tensions and capital structure on the firm value of multinational corporations listed on the Indonesia Stock Exchange during the 2021–2024 period. The research variables consist of the World Trade Uncertainty Index to represent global trade tensions, the Debt-to-Equity Ratio to capture capital structure, and Tobin’s Q ratio to measure firm value. The data were analyzed using multiple linear regression with 48 observations. The results indicate that the World Trade Uncertainty Index has a negative but insignificant effect on firm value, whereas the Debt-to-Equity Ratio has a positive and significant effect. These findings highlight that global trade uncertainty has not been strong enough to suppress the market value of companies, while optimal management of capital structure can enhance firm value. This study provides a theoretical contribution by reinforcing the perspectives of trade-off theory and signaling theory, and offers practical implications for financial managers and investors in designing financing strategies amid global uncertainty.